2019
DOI: 10.1186/s12879-019-4005-4
|View full text |Cite
|
Sign up to set email alerts
|

Association of HPV genotypes with external anogenital warts: a cross sectional study

Abstract: Background This study was undertaken to determine the distribution of type-specific human papillomavirus (HPV) in external anogenital warts, and the correlation with clinical presentation of warts and demographic data of patients. Methods Genital warts specimens were obtained from 129 men and 27 women attending a dermatology clinic, who had been advised surgical excision. The tissues were fixed and screened for HPV DNA by using real-time PCR. HPV genotype was determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 29 publications
2
21
0
Order By: Relevance
“…In line with this study, a cross-sectional study in Kuwait on 156 patients with genital warts showed that 102/156 (65.4%) of the patients were infected by LR-HPV and 54/156 (34.6%) of the patients were infected by HR-HPV. About 88.4% of the patients in the aforementioned study had single infection and 11.6% had multiple infections (Al-Awadhi et al, 2019). Another study in Spain showed that the frequency of LR-HPV infection was 63/138 (45.6%) in their patients and 71/138 (41.4%) of anogenital warts patients were infected by HR-HPV (Arroyo et al, 2016).…”
Section: P16 Ink4a Expression In Ca Lesionsmentioning
confidence: 80%
“…In line with this study, a cross-sectional study in Kuwait on 156 patients with genital warts showed that 102/156 (65.4%) of the patients were infected by LR-HPV and 54/156 (34.6%) of the patients were infected by HR-HPV. About 88.4% of the patients in the aforementioned study had single infection and 11.6% had multiple infections (Al-Awadhi et al, 2019). Another study in Spain showed that the frequency of LR-HPV infection was 63/138 (45.6%) in their patients and 71/138 (41.4%) of anogenital warts patients were infected by HR-HPV (Arroyo et al, 2016).…”
Section: P16 Ink4a Expression In Ca Lesionsmentioning
confidence: 80%
“…Blomberg et al indicated that the persistent HPV infection is the strongest risk factor for developing HPV-associated precancers and cancers [ 20 ]. The literature data indicate that patients with anogenital warts of one to six months duration were three times more likely to have oncogenic HPV infection compared to those with less than one month [ 7 , 21 ]. Hasanzadeh et al have shown that the coexistence of high-risk and low-risk HPV types infection may be associated with both an increased risk of the development of genital warts and the risk of persistent and recurrent HPV infections [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Those findings are confirmed by the results of our research, in which the presence of high-risk HPV types was associated with a worse clinical clearance rate and eradication rate of HPV ( p = 0.05, Figure 2 C) in comparison to the low-risk ones ( p = 0.0003). Thus, the HPV DNA detection is the indicator of the infection severity and the prognostic factor of treatment duration [ 5 , 7 , 12 ]. Wang et al made the duration of ALA-PDT treatment dependent on obtaining HPV DNA eradication confirmed by two negative tests [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been concluded that HPV carries a burden on almost a third of the communities worldwide. 5 , 2 Human papillomavirus has several genotypes, some of which are mainly responsible for the genital warts, namely genotypes 6 and 11. In contrast, the high-risk genotypes 16 and 18 are responsible for approximately 70% of all cervical cancers.…”
mentioning
confidence: 99%